Performance of an evacuated tube solar collector: technical report - Frick, David Murray, author; Karaki, Susumu, author; Solar Energy Applications Laboratory, Colorado State University, publisher (Colorado State University. Libraries, 1976)
Analysis of the performance characteristics of an evacuated tube solar collector is presented. Although the analysis is general enough to apply to other evacuated tube solar collectors, the work primarily concerns a prototype test module of a collector furnished by Corning Glass Works Company. A detailed theoretical analysis is presented along with the predicted performance of the test module. The theoretical analysis of the collector is given in two parts; the analysis of the optical characteristics of the glass tubes and the predictions of the thermal performance of the collector. Tests were made to compare the predicted with actual performance. Some test results are compared to the performance of a "conventional" flat-plate collector to show that the evacuated tube collector operates at greater collection efficiency. Analysis also shows that the performance of the collector can be increased by increasing the spacing between the tubes to allow for reflections onto the back sides of the absorber.
CER76-77 DMF-SK9.
Keywords: Solar energy -- Research; Heat engineering; Solar collectors